การศึกษาทักษะทางสังคมของนักเรียนระดับประกาศนียบัตรวิชาชีพ ประเภทวิชาพาณิชยกรรม: การวิจัยเชิงผสมผสาน - แสงเพชร, ลัดดา; เจริญกฤตยาวุฒิ, สรพงษ์; งามมีฤทธิ์, ณัฐกฤตา (วารสาร ศึกษาศาสตร์ มมร, 2019)
บทคัดย่อ การวิจัยแบบผสมผสานนี้มีวัตถุประสงค์ 1) เพื่อค้นหาองค์ประกอบของทักษะทางสังคมของนักเรียนระดับประกาศนียบัตรวิชาชีพ ประเภทวิชาพาณิชยกรรม จังหวัดชลบุรี และ 2) เพื่อตรวจสอบความสอดคล้องของโมเดลการวัดทักษะทางสังคมของนักเรียนระดับประกาศนียบัตรวิชาชีพ ประเภทวิชาพาณิชยกรรม กับข้อมูลเชิงประจักษ์ การวิจัยนี้จำแนกออกเป็น 2 ระยะ ได้แก่ ระยะแรก การวิจัยเชิงคุณภาพเพื่อค้นหาองค์ประกอบของทักษะทางสังคม ของนักเรียนระดับประกาศนียบัตรวิชาชีพ ประเภทวิชาพาณิชยกรรม จังหวัดชลบุรี โดยทำการเก็บรวบรวมข้อมูลด้วยการสัมภาษณ์กับผู้อำนวยการ/รองผู้อำนวยการ จำนวน 3 คน และครูผู้สอนจำนวน 4 คน ซึ่งพบว่าข้อมูลที่ได้จากการสัมภาษณ์มีความอิ่มตัวเป็นอย่างดี และข้อมูลที่ได้จะถูกนำมาวิเคราะห์ด้วยการวิเคราะห์ใจความหลัก ระยะที่สอง การวิจัยเชิงปริมาณเป็นการนำข้อค้นพบที่ได้จากการวิจัยเชิงคุณภาพ (ระยะที่ 1) ไปตรวจสอบยืนยันด้วยข้อมูลเชิงประจักษ์ด้วยการวิจัยเชิงปริมาณ ตัวอย่างในการศึกษา ได้แก่ นักเรียนที่กำลังศึกษาในระดับประกาศนียบัตรวิชาชีพ ประเภทวิชาพาณิชยกรรม จังหวัดชลบุรี ในปีการศึกษา 2561 เครื่องมือที่ใช้ในการศึกษา ได้แก่ แบบสอบถามซึ่งพัฒนาจากข้อค้นพบที่ได้จากผลการวิจัยเชิงคุณภาพ และการวิเคราะห์ข้อมูลใช้การวิเคราะห์องค์ประกอบยืนยันอันดับสอง ผลการวิจัยในส่วนของการการวิจัยเชิงคุณภาพ ด้วยการวิเคราะห์ใจความหลัก พบว่า ทักษะทางสังคมของนักเรียนระดับประกาศนียบัตรวิชาชีพ ประเภทวิชาพาณิชยกรรม ประกอบด้วย 7 องค์ประกอบหลัก ได้แก่ 1) การทำงานเป็นทีม 2) ความเป็นผู้นำ 3) การมีมนุษยสัมพันธ์ 4) การสื่อสาร 5) ความรับผิดชอบ 6) การจัดการตนเอง และ 7) การเห็นอกเห็นใจผู้อื่น และผลการวิจัยเชิงปริมาณด้วยการวิเคราะห์องค์ประกอบเชิงยืนยันอันดับสอง พบว่า โมเดลการวัดทักษะทางสังคมที่ได้จากผลการวิจัยเชิงคุณภาพมีความสอดคล้องกลมกลืนกับข้อมูลเชิงประจักษ์ในระดับดี Abstract The objectives of this mixed methods research were to explore the component of social skills among vocational certificate students majoring in commerce in Chonburi Province, Thailand, and to investigate the goodness of fit of the social skill model with the empirical data. The mixed methods research was divided into two main phases: a qualitative phase followed by a quantitative phase. In Phase I, qualitative research was conducted to investigate the component of social skills among vocational certificate students majoring in commerce in Chonburi Province. Data was collected from three college directors/deputy directors and four commerce teachers through an in-depth interview. Data obtained from a qualitative interview were rich and data saturation was achieved. Thematic analysis was utilized for qualitative data analysis. Phase II was the qualitative research which was to examine the consistency of the qualitative findings with quantitative data. Data was collected from vocational certificate students majoring in commerce who were currently enrolled in private vocational colleges in Chonburi Province in the academic year 2018. The research instrument was a questionnaire developed from the qualitative findings (Phase I). Data obtained from the survey was analyzed by using the second-order confirmatory factor analysis (CFA).  The qualitative research finding based on the thematic analysis revealed that the desirable social skills among vocational certificate students majoring in commerce consisted of seven main components: (i) teamwork, (ii) leadership, (iii) interpersonal relation, (iv) communication, (v) responsibility, (vi) self-management, and (vii) empathy. Furthermore, the quantitative research findings based on the second-order confirmatory factor analysis (CFA) revealed that the measurement model of social skills derived from the qualitative finding acceptably fitted with the empirical data.